DISCLOSURE OF IRS POST SEGMENT CONVERGENCE - Dian Surya Ayu Fatmawati; Bambang Subroto; Aulia Fuad Rahman (Universitas Muhammadiyah Malang, 2018)
The purpose of this study is to examine what extent of disclosure segmental reporting after IFRS convergence in Indonesia. The great value of this study is highlighted by the effort to empirically investigate the beginning impact of segmental disclosure standard to segment number. Descriptive analysis was used to describe changes of Line Of Business (LOB) segment, geographical segment, level of specificity number. The study consist of 32 Multinational company that listing in Indonesian Stock Exchange (ISE) at 2012-2017. Thus result show that number and types of segments reported decrease 4% for LOB and 2% for geographic segment and using more disaggregated at geographic level. Those findings about changing can help to lead an insight of segmental disclosure implementation in the future.